CREATIVE THINKING AND ITS ROLE IN ACHIEVING STRATEGIC LEADERSHIP: A FIELD STUDY SURVEYING THE OPINIONS OF A SAMPLE OF DEANS, ASSISTANT DEANS, HEADS OF DEPARTMENTS , AND DIVISION AND UNIT DIRECTORS IN SOME COLLEGES OF THI-QAR UNIVERSITY, IRAQ - Asst Inst. Sattar Awad Dhmaid (Galaxy International Interdisciplinary Research Journal, 2023)
This research aims to identify and interpret the nature of the correlation and influence between the independent variable of creative thinking and its variables (flexibility and originality) as a fundamental orientation for active institutions, and the dependent variable of strategic leadership and its variables (strategic leadership and entrepreneurial culture). Additionally, the study aims to explore the role of creative thinking in achieving strategic leadership among academic leaders in selected colleges of Thi-Qar University. The elements of creative thinking are analyzed and framed within an integrated conceptual framework, aiming to create strategic leadership capable of achieving strategic objectives in line with technological advancements and economic conditions. The research relies on a descriptive-analytical methodology and is conducted within the higher education and scientific research sector, specifically in five colleges of Thi-Qar University. A questionnaire was designed and distributed to a sample of 50 academic professors, including deans, assistant deans, department chairs, and division and unit directors. To achieve the research objectives, various statistical methods were employed, including means, standard deviations, t-tests, and F-tests. The required data were analyzed using the SPSS software. The research yielded several significant results, including the lack of significant attention by academic leaders in the studied colleges towards the strategic development of creative ideas among employees at all functional levels. The study also provided recommendations, such as the need for creative thinking not to be limited to specific colleges but to be adopted as an objective and strategic action plan that focuses on developing all aspects of the university and its formations. Furthermore, the study highlights the importance of Thi-Qar University investing more attention in developing high entrepreneurial capabilities to compete with newly established governmental and private universities in the province.